Current Status and Trends in Peptide Receptor Radionuclide Therapy in the Past 20 Years (2000–2019): A Bibliometric Study - Lu, Xiaojing; Lu, Cuncun; Yang, Yongjie; Shi, Xiangfen; Wang, Haibo; Yang, Nan; Yang, Kehu; Zhang, Xiaojian (Frontiers in Pharmacology, 2021)
Background: Peptide receptor radionuclide therapy (PRRT) is an emerging therapeutic option for the treatment of neuroendocrine tumors (NETs), and the number of publications in this field has been increasing in recent years. The aim of the present study was to present the research status and summarize the key topics through bibliometric analysis of published PRRT literature. Methods: A literature search for PRRT research from 2000 to 2019 was conducted using the Science Citation Index Expanded of Web of Science Core Collection (limited to SCIE) on August 4, 2020. The VOSviewer, R-bibliometrix, and CiteSpace software were used to conduct the bibliometric analysis. Results: From 2000 to 2019, a total of 681 publications (523 articles and 158 reviews) were retrieved. Annual publication outputs grew from three to 111 records. Germany had the largest number of publications, making the largest contribution to the field (n = 151, 22.17%). Active cooperation between countries/regions was observed. Kwekkeboom from the Erasmus Medical Center is perhaps a key researcher in the field of PRRT. The European Journal of Nuclear Medicine and Molecular Imaging and Journal of Nuclear Medicine ranked first for productive (n = 84, 12.33%) and co-cited (n = 3,438) journals, respectively. Important topics mainly included matters related to the efficacy of PRRT (e.g., 90Y-dotatoc and 177Lu-dotatate), the long-term adverse effects of PRRT (e.g., hematologic and renal toxicities), standardization of NETs and PRRT in practice, the development of medical imaging techniques, and the individual dose optimization of PRRT. Conclusion: Using bibliometric analysis, we gained deep insight into the global status and trends of studies investigating PRRT for the first time. The PRRT field is undergoing a period of rapid development, and our study provides a valuable reference for clinical researchers and practitioners.